2017
DOI: 10.1002/2017gl075032
|View full text |Cite
|
Sign up to set email alerts
|

Lower Mantle Substructure Embedded in the Farallon Plate: The Hess Conjugate

Abstract: The morphologies of subducted remnants in the lower mantle are essential to our understanding of the history of plate tectonism. Here we image a high‐velocity slab‐like (HVSL) anomaly beneath the southeastern U.S. using waveforms from five deep earthquakes beneath South America recorded by the USArray. In addition to travel time anomalies, the multipathing of S and ScS phases at different distances are used to constrain the HVSL model. We jointly invert S and ScS traveltimes, amplitudes, and waveform complexit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Liu et al (2008Liu et al ( , 2010 developed a reverse convection model for the locations of the plateaus over time. The reconstructed present-day location of the Hess plateau conjugate places the top just below the transition zone in the central United States, in agreement with subsequent seismic tomography models (e.g., Ko et al, 2017;Schmandt & Lin, 2014). The plateau has probably been in the vicinity of our study region since mid-Miocene, allowing for metasomatic reactions due to rising silica-rich fluids.…”
Section: 1029/2020jb020625supporting
confidence: 85%
“…Liu et al (2008Liu et al ( , 2010 developed a reverse convection model for the locations of the plateaus over time. The reconstructed present-day location of the Hess plateau conjugate places the top just below the transition zone in the central United States, in agreement with subsequent seismic tomography models (e.g., Ko et al, 2017;Schmandt & Lin, 2014). The plateau has probably been in the vicinity of our study region since mid-Miocene, allowing for metasomatic reactions due to rising silica-rich fluids.…”
Section: 1029/2020jb020625supporting
confidence: 85%
“…other regions, such as the Paleo-Tethys Ocean slab under India (e.g., Van der Voo et al, 1999;Zhao, 2015). In addition, a recent study of seismic waveform modeling has also confirmed the existence of the Hess Rise conjugate there (Ko et al, 2017).…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 89%
“…Seismic tomography shows three high‐velocity patches at ~871 km below the Great Lakes, the northern GOM, and the Caribbean (Simmons et al, ) (Figure ). The seismic anomaly below the northern GOM is characterized by sharp boundaries with a seismic shear‐wave velocity anomaly ( δV s ) elevated by 2.5% over a 50 km distance (Ko et al, ). This sharp seismic gradient cannot be explained by a cold Farallon slab, as thermal diffusion would reduce the gradient of δV s by ~7 times from that observed.…”
Section: Introductionmentioning
confidence: 99%